An Uncommon Case Report of Hypothyroidism, Type 1 Diabetes Mellitus, and Systemic Lupus Erythematosus with an Immunosuppressive Consequence: A Case Report - Hoda, Arif; Shinde, Shruti R; Chaudhari, Avinash; Vyahalkar, Sameer; Kulkarni, Amar; Binani, Pooja; Nagrik, Amit (Journal of Clinical Nephrology, 2024)
An autoimmune condition known as Systemic Lupus Erythematosus (SLE) affects several systems and manifests itself in a variety of ways. It is far more common among young women who are fertile. It has been demonstrated that a mix of environmental and genetic variables may trigger immunological responses, triggering T and B cells, and leading the B cells to overproduce pathogenic autoantibodies and dysregulate cytokines, which ultimately result in harm to many organs and tissues. One feature of SLE is the presence of antibodies against cytoplasmic and nuclear antigens. An autoimmune illness is also type 1 diabetes. β-cell antibodies (Ab) and other antibodies that cause the autoimmune death of the pancreatic β-cells, which make insulin, are part of the multifactorial pathophysiology of type 1 diabetes mellitus (T1DM). Immunosuppression is the therapy for systemic lupus erythematosus (SLE), and diabetes itself compromises immunity, making infections more opportunistic. We came across an unusual instance of a patient with SLE, T1DM, hypothyroidism on immunosuppression who subsequently acquired pulmonary TB. Key phrase: Autoimmune diseases such as type 1 diabetes mellitus (T1DM) and Systemic Lupus Erythematosus (SLE).